Pengaruh Product Placement Kopiko dalam Drama Korea terhadap Minat Beli Konsumen Generasi Muda - Villa, Caren; Utami, Lusia Savitri Setyo (Prologia, 2023)
Korean dramas are increasingly popular in Indonesia during the Covid-19 pandemic because they require people to be active at home. Indonesian companies like Kopiko take advantage of the popularity of Korean dramas to attract and retain consumers' memories of their products. This study aims to determine whether there is an effect of product placement in Korean dramas on the buying interest of young consumers. By using a quantitative approach, this study uses the method of distributing questionnaires to 45 respondents as a sample. The population in this study are consumers of generation Y and also generation Z with purposive sampling technique. This research raises a number of concepts, namely marketing communication, product placement, buying interest, and AIDDA theory. There are three data analysis techniques, namely normality test, simple regression analysis, hypothesis testing, validity test and reliability test. The results showed that Kopiko's product placement in Korean dramas affected the buying interest of young consumers by 63.2%. The most influential dimension in the independent variable (X) is the visual dimension and in the dependent variable (Y) the most affected is the psychological factor. Drama Korea semakin popular di Indonesia saat pandemi Covid-19 karena mengharuskan masyarakat beraktivitas dalam rumah. Perusahaan Indonesia seperti Kopiko memanfaatkan popularitas drama Korea untuk menarik minat dan mempertahankan ingatan konsumen terhadap produk mereka. Penelitian ini bertujuan mengetahui ada tidaknya pengaruh penempatan produk dalam drama Korea terhadap minat beli konsumen generasi muda. Dengan pendekatan kuantitatif, penelitian ini menggunakan metode penyebaran kuesioner kepada 45 responden sebagai sampel. Populasi dalam penelitian ini merupakan konsumen generasi Y dan juga generasi Z dengan teknik purposive sampling. Penelitian ini mengangkat sejumlah konsep yakni komunikasi pemasaran, product placement, minat beli, dan teori AIDDA. Terdapat tiga teknik analisis data yaitu uji normalitas, analisis regresi sederhana, uji hipotesis, uji validitas dan uji reliabilitas. Hasil penelitian menunjukkan bahwa product placement Kopiko dalam drama Korea berpengaruh terhadap minat beli konsumen generasi muda sebesar 63,2%. Dimensi yang paling berpengaruh dalam variabel bebas (X) adalah dimensi visual dan dalam variabel terikat (Y) yang paling terpengaruh yaitu faktor psikologis.